PERSPEKTIF PENDIDIKAN ISLAM TERHADAP TRADISI PERAYAAN MALAM 1 SURO - Khosi Saimima; Mudaimin Mudaimin; Azma Azma; Nursyam Nursyam; Samintang Samintang; Muspai Darahim (JURNAL TARBIYAH, 2025)
The tradition of the 1 Suro night is a Javanese cultural heritage with spiritual value, although some of its practices are viewed as not entirely aligned with Islamic teachings. This study aims to examine how Islamic education can provide a critical and contextual understanding so that the tradition remains consistent with Islamic values without abandoning local cultural identity. This research employs a descriptive qualitative approach using a case study method focused on the community of Petanusugi Village. Data were collected through participatory observation, in-depth interviews, and documentation. The data analysis involved the stages of reduction, presentation, and verification, supported by content and discourse analysis.The findings indicate that religious leaders, Islamic education teachers, and community members generally perceive the 1 Suro night tradition positively, as long as it does not contradict Islamic law. The tradition has the potential to serve as a medium for Islamic character education, particularly through values such as self-purification, spiritual awareness, maintaining social bonds, and strengthening monotheism. Activities such as public religious lectures and communal prayer serve as effective forms of integration between local culture and Islamic values.